Moses. [Videorecording] (NY : GT Media, 2010)
The Old Testament is filled with inspiring stories. But the story of Moses is perhaps, the greatest of them all. As the story begins, we learn that the Israelites-God's chosen people-have been enslaved by the ruler of Egypt. For many years, they labor without reward. But finally, God decides that he will put to an end to their oppression. He calls on one man -Moses - to lead his people to freedom.